2020
DOI: 10.3390/coatings10060601
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Resistance of Hard Coat Anodized AA 6061 in Citric–Sulfuric Solutions

Abstract: Aluminum is a material widely used in aeronautical and transport industries due to its excellent mechanical and corrosion resistance properties. Unfortunately, aluminum alloys are susceptible to corrosion, which limits their use in some corrosive environments. The aim of this work is to characterize hard coat film fabricated by anodizing in a citric–sulfuric acid system using electrochemical techniques. The anodization process was carried out using an aluminum alloy AA 6061 anodization bath: a mix of citric an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 49 publications
4
18
0
Order By: Relevance
“…Cyclic potentiodynamic polarization (CPP) and electrochemical noise (EN) measurements were conducted at room temperature using a Gill-AC potentiostat/galvanostat/ZRA (Zero Resistance Ammeter) from ACM Instruments (Manchester, UK) in 3.5 wt % NaCl and H 2 SO 4 solutions, with the latter reagent used to simulate acid rain conditions. A conventional three-electrode cell configuration was used for electrochemical corrosion studies, which consisted of a working electrode, WE (Titanium and its alloys), a reference electrode, RE (saturated calomel electrode (SCE), and a counter electrode, CE (platinum mesh) [57,58]. Corrosion tests were realized in triplicate.…”
Section: Electrochemical Measurementsmentioning
confidence: 99%
“…Cyclic potentiodynamic polarization (CPP) and electrochemical noise (EN) measurements were conducted at room temperature using a Gill-AC potentiostat/galvanostat/ZRA (Zero Resistance Ammeter) from ACM Instruments (Manchester, UK) in 3.5 wt % NaCl and H 2 SO 4 solutions, with the latter reagent used to simulate acid rain conditions. A conventional three-electrode cell configuration was used for electrochemical corrosion studies, which consisted of a working electrode, WE (Titanium and its alloys), a reference electrode, RE (saturated calomel electrode (SCE), and a counter electrode, CE (platinum mesh) [57,58]. Corrosion tests were realized in triplicate.…”
Section: Electrochemical Measurementsmentioning
confidence: 99%
“…All oxide layers exhibited porous structures. Alumina layers were usually formed in a hexagonal structure in a highly ordered honeycomb [4]. However, when alumina layers were hydrated the thin 'cornflake' structure would be formed at the surface of the oxide layer [17].…”
Section: Resultsmentioning
confidence: 99%
“…In detail, it was found that possible cathodic reactions to form the oxide layer in the acid sulfuric bath would be done as follows [2,4,27],…”
Section: Eds Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have found that the Warburg impedance in this type of material may be since the porous layer with high thicknesses becomes brittle and initially allows the ions to pass quickly. However, when they penetrate and reach the barrier layer, they make it difficult to continue penetrating and continue to accumulate [83]. The Warburg element controls the reaction rate through the diffusion of oxidizing and reducing species to and from the metal substrate.…”
Section: Cyclic Potentiodynamic Polarization (Cpp)mentioning
confidence: 99%